Adipsic Hypernatremic Myopathy (Iranian Journal of Kidney Diseases, 2015)
Chronic hypernatremia due to adipsia is very rare and occasionally presents with muscle weakness and rhabdomyolysis. We report a patient with chronic hypernatremia without thirst sensation who presented with muscle weakness and was treated successfully with prescribed water intake.